Preferential usage of rifaximin for the treatment of hydrogen-positive small intestinal bacterial overgrowth - Barkin, Jodie A (2019)
Objectives: Small intestinal bacterial overgrowth (SIBO) is challenging to treat and diagnose and is associated with diagnosisof irritable bowel syndrome (IBS). Although no FDA-approved medications exist for treatment of SIBO, rifaximin has recentlyreceived approval to treat diarrhea-predominant IBS and patients with methane-positive SIBO breath tests. The aim of thisstudy is to evaluate patient response to rifaximin for SIBO based on breath test results. Materials and methods: All patientsunderwent breath testing to evaluate for SIBO during a 42-month period. Patients were defined as having a positive glucosebreath test for SIBO based on an increase of ≥ 20 ppm of hydrogen and/or ≥ 10 ppm of methane 90 minutes after ingestingglucose. Patient demographic and symptom data, antibiotic treatment regimens, symptomatic response to therapy, and repeattreatments were recorded. Institutional review board approval was obtained. Results: A total of 53 of 443 patients had positivebreath testing for SIBO. Response rates to rifaximin (550 mg three times daily for 14 days) were 47.4% for hydrogen positivityalone and 80% for both hydrogen and methane positivity. Conclusions: Rifaximin was the most commonly prescribed antibioticregimen for SIBO therapy. Patients with hydrogen or hydrogen and methane positive breath tests responded well to rifaximintherapy. For patients with hydrogen-positive SIBO, rifaximin may prove a highly effective therapy in providing symptom relieffrom the effects of SIBO.